DESAIN DAN ANALISIS CASE LINFLOW WATER METER DENGAN MENGGUNAKAN METODE CAD - Nuryadi, Rio Arian Syaputra; Suryadi, Dedi; Nizam, Ahmad (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
Linflow water meter is a smart technology-based water consumption meter designed to improve accuracy and efficiency in water resource management, both in the household, commercial, and industrial sectors. To protect the sensitive components inside and ensure the durability of the tool in a wide range of environmental conditions, a reliable case design is required. This study aims to design and analyze the linflow water meter casing by considering the aspects of pressure resistance, protection against moisture and temperature, as well as conducting static and thermal analysis to evaluate the structural integrity and performance of the water meter, ensuring that it meets industry standards for efficiency and durability. The methodology used includes the selection of materials that are resistant to stress and corrosion, the design of ergonomic casing structures, and durability simulations using the finite element analysis (FEA) method. The results of the analysis show that the high-quality polymer material with the addition of an anti-corrosion coating provides optimal protection for the operational environment. In addition, the modular design of the case makes it easy to install and maintain without affecting the integrity of the device. These findings are expected to improve the design process and operational reliability of water meters, thereby supporting effective drainage management and infrastructure protection.